MAKNA MUJIZAT DALAM KITAB KELUARAN - Enggar Objantoro; Sabda Budiman (SAINT PAUL'S REVIEW, 2021)
Miracles are a phenomenon often found when reading the Bible. Miracles are also known as a form of the power of God shown through His chosen people. But in the supernatural event, there is a meaning contained. The book of Exodus is a book that tells a lot about miracles. Therefore, the question in this study is what do miracles mean in Exodus? Writing this scientific paper aims to explain the meaning of miracles in the book of Exodus. The authors used qualitative research methods with a descriptive approach. The data is obtained from various sources such as Bible commentary books, journal articles, and encyclopedia books. The result of the discussion in this study is the miracle of revealing the glory of God, deepening the knowledge of God, and miracles are interpreted as events that can foster the fear of God.